Pengaruh Pola Asuh Orangtua Terhadap Prestasi Belajar Dan Perilaku Sosial Peserta Didik SD Di Kecamatan Tamalanrea Kota Makassar - Ade Rahmi; Muhammad Yunus; Mas'ud Muhammadiah (Jounal of Primary Education, 2021)
Pola asuh dianggap menjadi faktor penentu terhadap kemampuan akademik dan kemampuan sosial anak, di antaranya adalah perilaku sosial dan prestasi belajar. Untuk itu peneliti tertarik untuk mengkaji secara ilmiah pengaaruh polaasuh orangtua terhadap perilaku sosial dan hasil belajar peserta didik SD di Kecamatan Tamalanrea Kota Makassar. Penelitian ini bertujuan untuk mendeskripsikan pola asuh yang di terapkan orangtua pada siswa SD, pengaruh pola asuh orangtua dalam membentuk perilaku sosial peserta didik SD, pengaruh pola asuh orangtua terhadap pretasi belajar peserta didik SD di Kecamatan Tamalanrea Kota Makassar dengan menggunakan Teknik analisis statistik deskriptif. Subjek penelitian ini adalah peserta didik kelas V Sekolah Dasar di Kecamatan Tamalanrea Kota Makassar Tahun ajaran 2020/2021 dengan jumlah siswa 50 orang. Hasil penelitian menunjukkan bahwa pola asuh yang banyak digunakan oleh orangtua di SD Kecamatan Tamalanrea Kota Makassar adalah pola asuh demokratis dan terdapat pengaruh dari pola asuh orangtua terhadap prestasi belajar dan perilaku sosial peserta didik SD di Kecamatan Tamalanrea Kota Makassar. Hal ini dibuktikan dengan adanya nilai prestasi belajar yang lebih baik pada buku laporan hasil belajar peserta didik yang diasuh dengan cara demokratis, sekaligus respondens terbanyak yaitu 28 orang (56%) dari 50 responden telah menjawab sangat setuju dengan pernyataan pola asuh demokratis orangtua sngat berpengaruh terhadap prestasi belajar seklah dasar di Kecamatan Tamalanrea Kota Makassar. Sehingga, Nilai Asymptotic Shig sebesar 0,000 yang artinya kurang dari Sig alpha yang ditentukan yaitu 5% (0,05) maka ada pengaruh yang signifikan dengan pengaaruh pola asuh orang tua terhadap prestasi belajar dan perilaku sosial peserta didik. Parenting is considered to be a determining factor for children's academic abilities and social abilities, including social behavior and learning achievement. For this reason, researchers are interested in scientifically examining the effect of parenting on social behavior and learning outcomes of elementary school students in Tamalanrea District, Makassar City. This study aims to: (1) describe the parenting styles applied by parents to elementary school students in Tamalanrea District, Makassar City, (2) describe the effect of parenting in shaping the social behavior of elementary school students in Tamalanrea District, Makassar City, and (3) describe the influence of parenting styles on the learning achievement of elementary school students in Tamalanrea District, Makassar City using descriptive statistical analysis techniques. The subjects of this study were students of grade V Elementary School (SD) in the Tamalanrea District of Makassar City for 2020/2021 academic year with 50 students. The results showed that the parenting style that is mostly used by parents in SD, Tamalanrea District, Makassar City is democratic parenting and there is an effect of parenting on learning achievement and social behavior of elementary school students in Tamalanrea District, Makassar City. This is evidenced by the existence of a better learning achievement value in the learning outcomes report book of students who are cared for in a democratic way, as well as the largest number of respondents, namely 28 people (56%) out of 50 respondents answered strongly agree with the statement that democratic parenting has an effect on learning achievement of elementary school students in the Tamalanrea District of Makassar City. The parenting style that can be a role model for all parents is democratic parenting, because it will make children confident and also easy to communicate with other individuals. The social behavior of students can be clearly illustrated in their daily life, especially at school. The communication and interaction built by students is reflected in the behavior patterns and habits they get at home, especially in social behavior. Thus, the Asymptotic Sig value is 0,000, which mean that it is less than the specified Sig alpha, which is 5 % (0.05), so there is a significant influence on the effect of parenting styles on learning achievement and social behavior of students.